The Effectiveness Of Substances In Growth Regulators On Growth Of Root Cutting Of Mother-In Law’s Tongue Leaves (Sansevieria trifasciata) - Ahmad Zainul Arifin; Fajar Hidayanto; Ridwan Isnaeni Mahfud (JURNAL AGRONOMI TANAMAN TROPIKA (JUATIKA), 2022)
Air pollution is often a major problem in industrial cities because it causes various respiratory diseases. Mother-in law’s tongue (Sansevieria trifasciata) is an ornamental plant that has many benefits. One of them is to help reducing the concentration of carbon monoxide gas in the air. In addition, this plant is easily propagated by cutting. The purpose of this study was to determine the effectiveness of natural and synthetic growth regulators (ZPT) with various doses on root growth of three materials from plant cuttings. This study used a completely randomized design (CRD) with three factors and three replications. The first factor was the type of ZPT, among others, shallot filtrate and Rootone-F. The second factor is the forth ZPT concentration. They are 25%, 50%, 75% and 100%. The third factor is the origin of the plant cuttings. If the collected data has a significant effect it would be further tested by using DMRT (Duncan Multiple Range Test) at a level of 5%. The results showed that the difference in ZPT had a significant effect on root length, but did not affect significantly the number of roots, fresh weight and dry weight. The treatment interaction had a very significant effect on the root length of Sansivera. The interaction with the highest value was found in the interaction of treatment with PGR type Rootone-F with a concentration of 100% with the cuttings originating from the middle of the plant, while the lowest was in the interaction between PGR type and onion filtrate with a concentration of 25% with the cuttings originating from the tip of the plant.